Vector bundles on Drinfeld symmetric spaces - Taylor, J (2024)
Let F be a finite extension of Qp, n ≥ 1, and let Ω be the (n−1)-dimensional Drinfeld symmetric space. In this thesis we study various vector bundles on Ω and its covering spaces that are of significance in the representation theory of GLn(F).